Efeito do uso contínuo de um protocolo de polimento mecânico no controle das alterações de superfície em dentes artificiais de resina acrílica - Barreto, Joel Oliveira (2017)
Acrylic resin is widely used for prosthodontics fabrication. Despite its many advantages, some changes in properties such as color stability and surface roughness can occur over the period of its use by the patients. In order to minimize those modifications, polishing procedures can be performed on the prosthesis’ surface, increasing its longevity and clinical performance and making them less susceptible to the action of external agents such as alimentary liquids and cleaning solutions. The aim is to evaluate the effect of a mechanical polishing protocol performed regurlarly in biofilm adhesion, surface roughness, color stability and mass of acrylic resin artificial teeth. Sixty upper central incisors were divided into two groups according to the immersion liquid (n=30) - distilled water and coffee; and these two groups subdivided into three subgroups (n = 10): A - only immersion; B – immersion associated with a fortnightly polishing; C – immersion associated with a monthly polishing. Mechanical polishing was performed using an aluminium oxide polishing paste and wheel of felt coupled to a manual engine at 3000 rpm for 5 seconds, at intervals of time simulating 15 and 30 days of daily consumption of coffee. Surface roughness, color and weight of the artificial teeth were evaluated before and after the interventions in intervals simulating 4, 8, 12 and 24 months. After this, it was assessed the adhesion of a Candida albicans and Streptococcus mutans biofilm in all groups. Results: After immersion in coffee, the specimens showed a significant increase in surface roughness and weight. The color changes observed for this group was significantly greater when compared with the group immersed in water. The tested polishing procedure reduced the roughness of the material and controlled the stains caused by coffee without losing mass, being the fortnightly frequency more effective than the monthly in controlling these changes. Also, the adhesion of biofilm was significantly reduced in the groups immersed in coffee after the polishing, being the fortnightly the most effective in controlling the amount of biofilm. Conclusion: When performed regularly, the mechanical polishing tested reduces the changes suffered by artificial teeth subjected to immersion in coffee, being the fortnightly frequency more effective in controlling the changes in the properties evaluated in this study.